2003
DOI: 10.1046/j.1365-2672.2003.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on Fusarium oxysporum f.sp. melonis survival during horticultural waste composting

Abstract: Aims: The aim of this work was to study the effect of high temperatures generated during composting process, on the phytopathogen fungus Fusarium oxysporum f.sp. melonis. This investigation was achieved by both in vivo (semipilot-scale composting of horticultural wastes) and in vitro (lab-scale thermal treatments) assays. Methods and Results: Vegetable residues infected with F. oxysporum f.sp. melonis were included in compost piles. Studies were conducted in several compost windrows subjected to different trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…If composting is done incorrectly (i.e. for too short a time or at too low a temperature), the result can increase microbial proliferation and risk of pathogen contamination 24, 25…”
Section: Main Sources Of Contamination Of Fresh Produce By Foodborne mentioning
confidence: 99%
“…If composting is done incorrectly (i.e. for too short a time or at too low a temperature), the result can increase microbial proliferation and risk of pathogen contamination 24, 25…”
Section: Main Sources Of Contamination Of Fresh Produce By Foodborne mentioning
confidence: 99%
“…[12] However, there is a lack of information on the fate of recombinant DNA in plants during composting. Our previous study indicated that heat-sensitive GM microorganisms and their transgenes were rapidly degraded during composting of organic wastes.…”
Section: Introductionmentioning
confidence: 99%
“…syringae Suárez-Estrella et al, 2007), and several viruses such as tomato spotted wilt virus (TSWV) and pepper mild mottle virus (PMMV) (Suárez-Estrella et al, 2002). Suárez-Estrella et al (2003) suggested that composting is therefore a useful method to recycle horticultural waste, when it is ensured that all pathogenic bacteria are eliminated in the process.…”
Section: Vegetable Waste Use As An Alternative and Friendly Substratementioning
confidence: 99%
“…In both cases, sawdust was added (1:4 ratio v/v), as a C/N relation conditioner. The composting process was described by Suárez-Estrella et al (2003), who indicated that piles of 2 m 3 were turned over and aerated periodically after the first 14 days of composting. Electrical conductivity (EC), anion content (NO 3 -, H 2 PO 4 -, SO 4 2-, Cl -) and cations (Ca 2+ , K + , Mg 2+ , Na + ) were determined by the saturation extract method (Warncke, 1986).…”
Section: Trace Metalsmentioning
confidence: 99%